Some convergence results for split common and fixed point problems in Hilbert space - Mohammed, L. B.; Kilicman, Adem; Auwalu, Abba (KOMUNITAS Analisis Matematika INDONESIA, 2022)
In this survey article, we present an introduction of split feasibility problems, multisets split feasibility problems and split common fixed point problems. Parallel and cyclic algorithms for solving the split common fixed point problems for finite family of strictly pseudocontractive mappings in Hilbert spaces are presented, weak and strong convergence theorems are being proved. Application of the split common fixed point problems and some numerical examples are also presented.